Preoperative carbohydrates: what is new? - Gianotti, Luca; Sandini, Marta; Hackert, Thilo (Current opinion in clinical nutrition & metabolic care, 2020)
Purpose of review The aim of this review is to give an overview of recently published articles covering preoperative carbohydrate loading in surgical patients. Recent findings Between January 1, 2017, and December 31, 2019, 26 publications addressing the effect of carbohydrate load were retrieved through a systematic search. Seventeen were randomized clinical trials, three prospective observational studies and six retrospective series with case-control comparison. Most of the studies were underpowered, addressed surrogate endpoints, and variability among dose and timing of carbohydrate (CHO) treatment was high. The most recent literature endorses preoperative carbohydrate loading up to 2 h before operations as a safe treatment. The new evidence confirm that this strategy is effective in reducing perioperative insulin resistance and the proportion of hyperglycemia episodes, and improving patient well-being and comfort but without affecting surgery-related morbidity. Further properly designed randomized clinical trials, addressing more clinically relevant endpoints such as length of hospitalization and morbidity rate, are warrant.
Gesehen am 05.08.2020